New Species of the Genus Circumoncobothrium (Shinde, 1968) (Cestoda: Pseudophyllidea carus, 1863) from a Fresh Water Fish, Osmanabad, India - Jaywant S. Dhole, Karmveer N. Kadam1* and (Recent Research in Science and Technology, 2011)
The present paper deals with a new species of the genus Circumoncobothrium Shinde, [16], Viz Circumoncobothrium clariasi n. sp is recovered from freshwater fish Clarias batrachus (L.) at Tulajapur, Dist. Osmanabad. The present form differs from all other known species of the genus having in the shape and size of the scolex, hooks 48 in number, total number and arrangement of testes, position of cirrus pouch, ovary is dumbbell shaped, vitellaria follicular and opening of the genital pore.